Penguatan Ideologi Pancasila di Kalangan Mahasiswa dan Masyarakat - Siti Patimah; Andika Putra Ramadhan; Annisa Salina Bardury; Fadilla Rizky; Martsya Putri Analya; Penty Yuliasty; Reno Alpa Lopi (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The purpose of this study was to determine the level of knowledge and understanding of the value of Pancasila ideology among students and the community. This study uses descriptive quantitative research methods. The results showed that almost all respondents implementing Pancasila in the first precept among students were good and maximal. This can bring goodness to the nation's future successors to become individuals with noble character and high dedication to the country. The respondents (new students) already fully have and apply their obligations to God Almighty in their daily lives. The conclusion is that most students and the community have implemented the values of Pancasila Keywords: Pancasila, Society, Students, Strengthening, Values.